2011
DOI: 10.1155/2011/713867
|View full text |Cite
|
Sign up to set email alerts
|

C16-Ceramide Analog Combined with Pc 4 Photodynamic Therapy Evokes Enhanced Total Ceramide Accumulation, Promotion of DEVDase Activation in the Absence of Apoptosis, and Augmented Overall Cell Killing

Abstract: Because of the failure of single modality approaches, combination therapy for cancer treatment is a promising alternative. Sphingolipid analogs, with or without anticancer drugs, can improve tumor response. C16-pyridinium ceramide analog LCL30, was used in combination with photodynamic therapy (PDT), an anticancer treatment modality, to test the hypothesis that the combined treatment will trigger changes in the sphingolipid profile and promote cell death. Using SCCVII mouse squamous carcinoma cells, and the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Cell survival was assessed using clonogenic assay according to the modified pre-plating protocol, as we described in [22]. Cells were resuspended in growth medium containing Pc4 (20 nM) and seeded (250 cells/well) in a 6-well plate (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Cell survival was assessed using clonogenic assay according to the modified pre-plating protocol, as we described in [22]. Cells were resuspended in growth medium containing Pc4 (20 nM) and seeded (250 cells/well) in a 6-well plate (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…For PDT experiments, after overnight incubation with Pc 4 (250 nM) at 37°C, cells were irradiated with red light (2 milliwatts/cm 2 ; λ max ~ 670 nm) using a light-emitting diode array light source (EFOS) at the fluence of 200 mJ/cm 2 at room temperature. The PDT dose (250 nM Pc 4 + 200 mJ/cm 2 ) used in our studies was chosen based on our previous findings [16]. Pc 4 alone had no effect on any biological outcome tested in the presented studies.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that combining Pc 4-PDT with the cationic C16-ceramide analog LCL30 led to augmented overall killing of mouse SCCVII squamous carcinoma cells (SCCVII cells) [16]. LCL85, a cationic B13 SL analog, is a promising anticancer agent [17].…”
Section: Introductionmentioning
confidence: 99%
“…This appears not to be the case with LCL30 since similar percentages of apoptotic cancer cells were found in SCCVII tumors treated by PDT alone or PDT combined with LCL30. Our in vitro studies with SCCVII cells revealed that combining PDT with LCL30 enhanced global ceramide level increase, caspase-3 activation, and overall cell killing in the absence of apoptosis [21]. However, these in vitro results were obtained with Pc4-PDT and it remains to be seen to what extent they are mimicked by Photofrin-PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional SL modulators, LCL30 (C16-ceramide analogue)[19] and LCL85 (acid ceramidase inhibitor B13 analogue)[20] were examined in vitro combined with PDT and were both found to augment PDT-mediated killing of SCCVII cells [21,22]. These cationic, mitochondrially-targeted compounds were originally developed as potential anticancer agents [23 24…”
Section: Introductionmentioning
confidence: 99%